Weekly paclitaxel treatment in the first-line therapy of classic Kaposi sarcoma: A real-life study. Issue 5 (3rd February 2023) - Paksoy, Nail; Khanmammadov, Nijat; Doğan, İzzet; Ferhatoğlu, Ferhat; Ahmed, Melin Aydan; Karaman, Sule; Aydiner, Adnan
Abstract : Kaposi sarcoma is an angioproliferative disease associated with human herpes virus 8 infection. Classic Kaposi sarcoma (CKS) usually develops in older age. Although CKS often does not require systemic therapy, systemic therapy can be administered in progressively symptomatic patients. In this real-life study, we purposed to determine effectiveness and safety of weekly paclitaxel therapy in the first-line treatment of CKS. In this cross-sectional retrospective study, we analyzed the clinical data of 44 patients with CKS who received first-line paclitaxel therapy between January 2000 and December 2020. Paclitaxel was administered by intravenous infusion 80 to 100 mg/weekly. The median age of the patients was 67 years (range, 39–86 years), and majority male (77.2%). All patients had cutaneous involvement in extremities. The median follow-up time from paclitaxel treatment was 39.1 (range, 3.7–173.5) months. The median progression free survival from start of therapy was 35.1 months (range, 2–144 months). Complete response, partial response and stable disease were observed in 7 (15.9%), 28 (63.7%) and 6 (13.6) patients, respectively. Objective control rate was 79.6%, and the median response time after the last dose of paclitaxel was 18.2 months. A total of 4 patients (9.1%) had grade 3 to 4 neutropenia, but it was not complicated by febrile neutropenia. Three patients (6.8%) experienced grade 3 to 4 peripheral neuropathy. No patient had grade 3 to 4 allergic reaction. There was no drug-related death. According to our results, paclitaxel is an effective therapy option with an acceptable safety profile for patients with advanced CKS.